MXene-based electromagnetic shielding material for anchoring 0 / 2-dimensional magnetic metal as well as preparation and application of MXene-based electromagnetic shielding material
By embedding magnetic alloy microspheres and sheet magnetic metals in MXene materials, the electromagnetic shielding material is formed, and the problems of easy corrosion, large volume and single loss mechanism of electromagnetic shielding materials in the prior art are solved, and a rich electromagnetic loss mechanism and Broadband shielding effect, suitable for a variety of electronic devices.
Patent Information
- Application Number
- CN202411394759.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-08
AI Technical Summary
Due to the easy corrosion, large volume, non-magnetic and single electromagnetic loss mechanism, existing electromagnetic shielding materials are difficult to meet the electromagnetic shielding requirements in the broadband direction. The process of introducing magnetic metal particles into MXene is complicated and the components are difficult to control.
Using an MXene-based electromagnetic shielding material anchored by 0/2-dimensional magnetic metal, the MXene-based electromagnetic shielding material is embedded in the MXene material with nearly 0-dimensional magnetic alloy microspheres and 2-dimensional sheet magnetic metal, and mixed with anionic surfactant and ultrasonic process to form electromagnetic The mass ratio of shielding materials, magnetic alloy microspheres and sheet magnetic metals is adjustable.
It has achieved rich electromagnetic loss mechanism, large shielding bandwidth, simple preparation method, and can significantly improve electromagnetic shielding efficiency within a wide frequency band range. It is suitable for scenarios such as MEMS sensors, automotive electronic products and stealth fighters.
Smart Images

Figure CN119277742A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electromagnetic shielding composite materials, and in particular to a MXene-based electromagnetic shielding material anchored with a 0 / 2-dimensional magnetic metal, and a preparation method and application thereof. Background Art
[0002] The rapid development of wireless communication technology has greatly promoted the popularity of electronic devices in daily life. However, it has also generated a large amount of electromagnetic pollution, which not only affects human health, but also interferes with the normal use of sensors and precision electronic equipment, affecting their measurement accuracy. Therefore, the preparation of efficient electromagnetic shielding materials is crucial to improving the electromagnetic environment, ensuring the normal operation of electronic equipment, and improving the measurement accuracy of precision measuring equipment. At the same time, with the widespread application of centimeter and millimeter waves in modern information technology, electromagnetic shielding materials will further develop in the direction of broadband. However, traditional electromagnetic shielding materials, such as metals and conductive polymers, are difficult to meet these requirements due to their shortcomings such as susceptibility to corrosion, large size, non-magneticity, and single electromagnetic loss mechanism. In recent years, researchers have explored various electromagnetic loss materials, including carbon nanotubes, graphene, silver nanowires, zinc oxide, metal organic frameworks, silicon carbide, and molybdenum disulfide. However, the electromagnetic loss mechanism generated by these materials is single, and the electromagnetic waves will be reflected due to impedance mismatch, causing secondary pollution.
[0003] MXene, a two-dimensional material with high conductivity, has become the most promising electromagnetic shielding material due to its strong electromagnetic wave dissipation ability. MXene is a new type of two-dimensional material composed of transition metal carbides, nitrides or carbonitrides with a conductivity of about 2.4×10 5 S / m, much higher than graphene. In addition, MXene has a unique layered structure, rich surface groups and a high specific surface area, so it exhibits high electromagnetic shielding performance. However, due to its non-magnetic properties, limited attenuation mechanism and ultra-high conductivity, the electromagnetic parameters are unbalanced, making it impossible to achieve good impedance matching, which means that electromagnetic waves cannot be effectively absorbed and dissipated. Therefore, although pure MXene has high potential in the field of electromagnetic shielding, it is not suitable for direct use as an electromagnetic shielding material. Magnetic metal particles such as nickel, cobalt and nickel-cobalt alloys are considered to be strong candidate materials for enhancing electromagnetic wave attenuation due to their high Snoek limit, high magnetic permeability and high magnetic saturation induction intensity in the GHz range. Introducing magnetic particles into two-dimensional MXene is an effective way to change its impedance matching characteristics and enrich its electromagnetic loss capacity. However, the current process of introducing magnetic particles into MXene is complicated, the introduced mass composition is not easy to control, and most of them are particle shapes with a single loss mechanism.
[0004] Therefore, there is an urgent need to explore an electromagnetic shielding composite material with a simple preparation method, easy to control the quality of the introduction of magnetic metal particles, rich electromagnetic loss mechanisms, and a large shielding bandwidth. Summary of the invention
[0005] In view of the defects in the prior art, the purpose of the present invention is to provide a MXene-based electromagnetic shielding material anchored with 0 / 2-dimensional magnetic metals, and its preparation and application. The electromagnetic shielding material provided by the present invention has rich electromagnetic loss mechanisms, a large effective shielding bandwidth, a simple preparation method, and easy-to-control component ratios.
[0006] According to a first aspect of the present invention, a MXene-based electromagnetic shielding material anchoring a 0 / 2-dimensional magnetic metal is provided, wherein the electromagnetic shielding material comprises a MXene material, nearly 0-dimensional magnetic alloy microspheres and a 2-dimensional flaky magnetic metal, wherein the MXene material has a lamellar structure, and the magnetic alloy microspheres and the flaky magnetic metal are embedded between the lamellar layers of the MXene material, and the mass of the magnetic alloy microspheres accounts for 8.3%-33.3% of the total mass of the electromagnetic shielding material, and the flaky magnetic metal accounts for 8.3%-33.3% of the total mass of the electromagnetic shielding material.
[0007] Optionally, the MXene material is a MAX phase ceramic.
[0008] Optionally, the particle size of the MXene material is 200-400 mesh.
[0009] Optionally, the magnetic alloy microspheres are any one of magnetic FeCo microspheres, magnetic CoNi microspheres and magnetic FeNi microspheres.
[0010] Optionally, the diameter of the magnetic alloy microspheres is 1-10 μm.
[0011] Optionally, the flaky magnetic metal is any one of nano-flaky nickel, nano-flaky iron and nano-flaky ferroferric oxide.
[0012] Optionally, the side length of the sheet-shaped magnetic metal is 1-20 μm.
[0013] According to a second aspect of the present invention, a method for preparing an anchored 0 / 2-dimensional magnetic metal MXene-based electromagnetic shielding material is provided, the preparation method comprising:
[0014] Providing a MXene suspension;
[0015] Adding magnetic alloy microspheres into deionized water, then adding anionic surfactant, and ultrasonically dispersing to obtain a magnetic alloy microsphere dispersion;
[0016] Adding flaky magnetic metal powder into deionized water, adding anionic surfactant, and ultrasonically dispersing to obtain flaky magnetic metal dispersion;
[0017] The MXene suspension, the magnetic alloy microsphere dispersion and the flaky magnetic metal dispersion are mixed and uniformly dispersed by ultrasonication to obtain a composite liquid;
[0018] Rapidly freezing the composite liquid with liquid nitrogen to form a shape;
[0019] The freeze-formed mixture is vacuum dried to obtain anchored 0 / 2-dimensional magnetic metal MXene-based electromagnetic shielding material powder.
[0020] Optionally, providing a MXene suspension comprises: adding MAX phase ceramic powder to an etching solution, stirring in a water bath, then centrifugally washing, and then ultrasonically dispersing to obtain a MXene suspension.
[0021] Optionally, the etching solution is a HCl / LiF composite solution.
[0022] Optionally, the anionic surfactant is any one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and sodium diethylhexyl sulfosuccinate.
[0023] According to a third aspect of the present invention, there is provided an application of the MXene-based electromagnetic shielding material of the first aspect or the MXene-based electromagnetic shielding material prepared by the method of the second aspect, wherein the electromagnetic shielding material is applied to any one of MEMS sensor packaging, automotive electronic products, stealth fighters and wearable electronic devices.
[0024] Compared with the prior art, the present invention has at least one of the following beneficial effects:
[0025] 1. The present invention forms a MXene-based electromagnetic shielding material by introducing nearly 0-dimensional magnetic alloy microspheres and 2-dimensional flaky magnetic metals into MXene materials. The MXene material provides dielectric loss and multiple reflection loss capabilities, and the nearly 0-dimensional magnetic alloy microspheres and 2-dimensional flaky magnetic metals provide magnetic loss and reflection loss. Therefore, not only can the magnetic loss capacity of the electromagnetic shielding material be compensated, but the 2-dimensional flaky magnetic metal can also reflect electromagnetic waves like MXene nanosheets, increase the propagation path of electromagnetic waves, and further enhance the electromagnetic wave attenuation ability of the material. The MXene-based electromagnetic shielding material provided by the present invention has rich electromagnetic loss mechanisms, has high electromagnetic shielding capability in a wider frequency band, and has significant electromagnetic shielding effectiveness.
[0026] 2. The present invention directly uses anionic surfactants and ultrasonic technology to mix MXene with magnetic alloy microspheres and flaky magnetic metals. Different from the chemical composite process, the method of the present invention can more accurately adjust the ratio between different elemental materials. The direct composite method is simple in process and easy to control the ratio of various components, thereby facilitating the preparation of electromagnetic shielding materials with good shielding effectiveness.
[0027] 3. The electromagnetic shielding material prepared by the present invention can be applied as a coating, as a filling material or prepared into a composite film, so that it can be used in multiple scenarios. The MXene-based electromagnetic shielding material provided by the present invention has a large effective shielding bandwidth and significant electromagnetic shielding performance, and has broad application prospects in MEMS sensor packaging, automotive electronic products, stealth fighters, and wearable electronic devices in anti-electromagnetic interference. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0029] Figure 1 This is a schematic structural diagram of a MXene-based electromagnetic shielding material anchored with a 0 / 2-dimensional magnetic metal in Example 1 of the present invention;
[0030] Figure 2 This is a scanning electron microscope image of the MXene-based electromagnetic shielding material powder anchored with 0 / 2-dimensional magnetic metal in Example 1 of the present invention;
[0031] Figure 3 This is a diagram of the electromagnetic shielding effectiveness of the MXene-based electromagnetic shielding material anchored with a 0 / 2-dimensional magnetic metal in Example 1 of the present invention in the range of 2 to 18 GHz;
[0032] Figure 4 This is a diagram of the electromagnetic shielding effectiveness of the MXene-based electromagnetic shielding material anchored with a 0 / 2-dimensional magnetic metal in Example 2 of the present invention in the range of 2 to 18 GHz;
[0033] Figure 5 This is a diagram of the electromagnetic shielding effectiveness of the MXene material in the comparative example of the present invention in the range of 2 to 18 GHz. DETAILED DESCRIPTION
[0034] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0035] An embodiment of the present invention provides a MXene-based electromagnetic shielding material anchoring a 0 / 2-dimensional magnetic metal. Specifically, the electromagnetic shielding material includes a MXene material, nearly 0-dimensional (i.e., close to 0-dimensional) magnetic alloy microspheres, and a 2-dimensional flaky magnetic metal. The MXene material presents a large-surface-area flaky structure, which provides dielectric loss and multiple reflection loss capabilities. The magnetic alloy microspheres and the flaky magnetic metal provide magnetic loss and reflection loss. Since the MXene material has a lamellar structure, the magnetic alloy microspheres and the flaky magnetic metal are embedded between the lamellar layers of the MXene material. The mass of the magnetic alloy microspheres accounts for 8.3%-33.3% of the total mass of the electromagnetic shielding material, and the flaky magnetic metal accounts for 8.3%-33.3% of the total mass of the electromagnetic shielding material.
[0036] In some preferred embodiments, in the MXene-based electromagnetic shielding composite material, the addition amount of the magnetic alloy microspheres is 16.7%-25%, and the addition amount of the flaky magnetic metal is 16.7%-25%.
[0037] In the embodiment of the present invention, the amount of magnetic alloy microspheres added is set according to their influence on the conductivity of the composite material and the magnetic loss. The appropriate addition ratio can improve the impedance mismatch caused by the ultra-high conductivity of the MXene material itself, thereby enhancing the absorption of electromagnetic waves. At the same time, due to the magnetism of the magnetic alloy microspheres themselves, the composite material has a certain magnetic loss capacity. The amount of flaky magnetic metal added is determined according to its influence on the conductivity, magnetic loss, and reflection loss of the composite material. In addition to having the same functions as the above-mentioned magnetic alloy microspheres, the flaky magnetic metal can reflect electromagnetic waves and enhance the shielding performance of the composite material due to its own special flaky structure.
[0038] When the percentage of magnetic alloy microspheres and flaky magnetic metals in the total mass of the composite material is set to 8.3%-33.3%, preferably, 16.7%-25%, it will not have a significant impact on the conductivity of the composite material, and will also achieve better impedance matching characteristics, with the best coordination of conductive loss and magnetic loss, and better electromagnetic shielding performance. In contrast, if the amount of magnetic particles (magnetic alloy microspheres and flaky magnetic metals) added is too small, the high conductivity of the original MXene material will be destroyed, and the magnetic loss capacity provided by it cannot make up for the lost shielding performance; and too high a doping amount of magnetic particles will cause agglomeration, greatly reducing the shielding properties of the composite material.
[0039] In some embodiments, the MXene material is a MAX phase ceramic, which can be made of Ti 3 AlC 2 , Nb 2 AlC、V 2 AlC、Ti 3AlCN and other materials. MAX phase ceramic material is a ternary layered compound, in which: M represents transition metals, such as titanium, niobium, molybdenum, etc.; A represents main group elements, such as aluminum, silicon, tin, etc.; X represents carbon or nitrogen. These three elements are arranged in a certain proportion and structure to form a material with a hexagonal layered structure. The MXene material obtained by subsequent etching using MAX phase ceramic materials has the advantages of large surface area, high conductivity, and rich surface functional groups. The high conductivity of MXene will reflect electromagnetic waves to a great extent, and the electromagnetic waves incident on the surface of the material will also cause conductive losses; its unique sheet structure will also reflect electromagnetic waves, causing further dissipation of electromagnetic waves, and its own surface groups can be used as polarization sites to cause polarization losses, so MXene is a relatively potential electromagnetic shielding material. The particle size of the MXene material is mainly determined by the surface area of the flake MXene formed after etching. In theory, a large surface area will provide more attachment sites for magnetic alloy microspheres and flake magnetic metals, and it is also easier to form a good conductive path and reflect electromagnetic waves to a greater extent. Preferably, the particle size of the MAX material for preparing MXene is 200-400 mesh.
[0040] For example, the MAX material for preparing MXene is Ti with a particle size of 200 mesh. 3 AlC 2 .
[0041] In some embodiments, the magnetic alloy microspheres are any one of magnetic FeCo microspheres, magnetic CoNi microspheres, and magnetic FeNi microspheres. On the one hand, the impedance mismatch phenomenon caused by the high conductivity of the pure MXene sample itself can be reduced, and at the same time, the magnetic loss capacity of the composite material can be enriched. The diameter of the magnetic alloy microspheres mainly considers whether it will destroy the conductivity of the original MXene material. If the diameter is too large, it will cause great damage to the flaky morphology of the MXene material, thereby greatly damaging the conductive path of the composite material and causing a decrease in electromagnetic shielding performance. Preferably, the diameter of the magnetic alloy microspheres is 1-10 μm.
[0042] Exemplarily, the magnetic alloy microspheres are FeCo alloys, and the diameter of the FeCo alloy microspheres is 1-2 μm.
[0043] In some embodiments, the sheet magnetic metal is any one of nano-sheet nickel, nano-sheet iron and nano-sheet ferroferric oxide. These materials have high magnetic permeability, and the sheet structure is easy to process, which can effectively improve the impedance matching characteristics of the composite material, enrich the magnetic loss capacity, and the sheet structure can further reflect electromagnetic waves. The side length of the sheet magnetic metal mainly considers its influence on the conductive path and the influence on the reflection loss of electromagnetic waves. The side length should not be too small, otherwise it will not reflect electromagnetic waves, and the side length should not be too large to avoid stacking with MXene sheets and destroying the conductive path. Preferably, the side length of the sheet magnetic metal is 1-20 μm.
[0044] Exemplarily, the flaky magnetic metal is nano-flaky Ni, and the side length of the nano-flaky Ni is 1-5 μm.
[0045] The electromagnetic shielding materials in the above embodiments of the present invention include dielectric loss material MXene, nearly 0-dimensional magnetic alloy microspheres and nearly 2-dimensional flaky magnetic metals. Due to its good electrical conductivity, unique layered structure and surface groups, MXene materials can cause ohmic loss, interface polarization loss and multiple reflection loss. Zero-dimensional alloy microspheres can reduce the high conductivity caused by MXene in the composite material and improve the impedance matching characteristics. At the same time, under the action of alternating electromagnetic waves, they can also resonate naturally and exchange resonance loss electromagnetic waves with other magnetic alloy microspheres. In addition to providing magnetic loss capabilities, flaky magnetic metals can also reflect electromagnetic waves like MXene materials, increase the propagation path of electromagnetic waves, and further enhance the electromagnetic wave attenuation capability of the composite material. The composite material provided by the embodiment of the present invention has rich electromagnetic loss mechanisms, and the composite material has a high electromagnetic shielding capability in a wider frequency band, and the electromagnetic shielding effectiveness is significant.
[0046] The embodiment of the present invention provides a method for preparing the above-mentioned MXene-based electromagnetic shielding composite material anchored with 0 / 2-dimensional magnetic metal, comprising:
[0047] S1, providing a MXene suspension;
[0048] S2, adding the magnetic alloy microspheres to deionized water, and then adding an anionic surfactant, illustratively, the anionic surfactant is sodium dodecylbenzene sulfonate (SDBS), sodium dodecyl sulfate, sodium dioctyl sulfosuccinate, etc., and ultrasonically dispersing to obtain a magnetic alloy microsphere dispersion;
[0049] S3, adding flaky magnetic metal powder to deionized water, and then adding an anionic surfactant, illustratively, the anionic surfactant is sodium dodecylbenzene sulfonate, and ultrasonically dispersing to obtain a flaky magnetic metal dispersion;
[0050] S4, mixing the MXene suspension, the magnetic alloy microsphere dispersion and the flaky magnetic metal dispersion, and uniformly dispersing them by ultrasonication to obtain a composite liquid;
[0051] S5, rapidly freezing the composite liquid with liquid nitrogen to form a shape;
[0052] S6. The freeze-formed mixture is placed in a freeze dryer for vacuum drying to obtain a MXene-based electromagnetic shielding material powder anchored with a 0 / 2-dimensional magnetic metal.
[0053] The above embodiment of the present invention directly uses anionic surfactants such as sodium dodecylbenzene sulfonate to composite different proportions of magnetic alloy microspheres and flaky magnetic metals onto MXene materials. When the anionic surfactant contacts the deionized water in the solution, it will ionize anions and be tightly adsorbed by the surface of the magnetic particles, which are called surface ions. In the aqueous medium, ions with opposite charges are called counterions. Some counterions are adsorbed by surface ions through electrostatic adsorption, and are tightly bound to magnetic particles and surface ions, which are called bound counterions, forming a tight layer, and they become a moving whole in the aqueous medium. Another part of the counterions is dispersed around to form a diffusion layer. The -OH and -F functional groups introduced into the MXene material during the preparation process make it negatively charged, so that it will be compounded with positively charged magnetic particles under electrostatic adsorption; then the composite liquid is quickly freeze-dried with liquid nitrogen, and finally the MXene / magnetic alloy microsphere / flaky magnetic metal composite material is prepared by freeze-drying. The direct composite method used in the embodiment of the present invention has a simple preparation process and is easy to control the proportion of various components.
[0054] In some embodiments, a MXene suspension is provided, comprising: adding MAX phase ceramic powder to an etching solution, stirring in a water bath, then centrifugally washing, and then ultrasonically dispersing to obtain a MXene suspension.
[0055] In some embodiments, the etching solution is a HCl / LiF composite solution.
[0056] In the above embodiment of the present invention, the ultrasonic power should not be too large, and the time can be appropriately extended. For example, in steps S2 to S4, the ultrasonic power is 160W and the ultrasonic time is 15 minutes.
[0057] Ti 3 C 2 T x MXene / FeCo / Ni composite material as an example, Ti 3 C 2 T x The preparation method of MXene / FeCo / Ni composite material comprises the following steps:
[0058] S1. Stripping Ti by configuring HCl / LiF etching solution 3 AlC 2 Get Ti 3 C 2 T x Nanosheets are then prepared into Ti 3 C 2 T x MXene nanosheet dispersion;
[0059] S2, adding FeCo alloy particles into deionized water, adding SDBS, and ultrasonically dispersing to obtain a FeCo alloy particle dispersion;
[0060] S3, adding Ni flake powder into deionized water, adding SDBS, and ultrasonically dispersing to obtain Ni flake dispersion;
[0061] S4, the Ti obtained in step S1 3 C 2 T x The MXene suspension is mixed with the FeCo alloy dispersion obtained in step S2 and step S3 and the Ni flake dispersion, and then ultrasonically dispersed to obtain Ti 3 C 2 T x MXene / FeCo / Ni mixed dispersion;
[0062] S5, rapidly freezing the uniform dispersion obtained in step S4 with liquid nitrogen;
[0063] S6, placing the frozen mixture obtained in step S5 in a freeze dryer and vacuum drying for 36 hours to obtain Ti 3 C 2 T x MXene / FeCo / Ni composite powder.
[0064] Different from the chemical composite process, the above embodiment of the present invention directly uses anionic surfactants and subsequent ultrasonic processes to mix MXene and magnetic metals. The process is simple and the ratio between different elemental materials can be adjusted more accurately, thereby solving the problem of complicated preparation process of embedding magnetic particles between MXene layers and difficult control of sample content.
[0065] The embodiment of the present invention provides an application of a MXene-based electromagnetic shielding material. By introducing magnetic alloy microspheres with low coercivity and high saturation magnetization and flaky magnetic metals into the composite material, not only can the magnetic loss capacity of the composite material be compensated, but the flaky magnetic metal can also reflect electromagnetic waves like MXene nanosheets, increase the propagation path of electromagnetic waves, thereby further enhancing the electromagnetic wave attenuation ability of the composite material, and the electromagnetic loss mechanism is rich, with a large effective shielding bandwidth and significant electromagnetic shielding effectiveness, making it a promising candidate material in electromagnetic shielding applications. The composite material in the above embodiment of the present invention can be applied as a coating, as a filling material or prepared into a composite film, so as to be applied in multiple scenarios. The above composite material can be applied to any one of high-precision MEMS sensor packaging, automotive electronic products (automotive chips), stealth fighters and wearable electronic devices to achieve a good electromagnetic shielding packaging effect.
[0066] The scheme of the present application will be explained below in conjunction with specific embodiments and comparative examples. It will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product specification are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained through commercial channels.
[0067] Example 1
[0068] The MXene-based electromagnetic shielding material anchored with a 0 / 2-dimensional magnetic metal provided in this embodiment, wherein the FeCo alloy particles account for 25% of the total mass of the electromagnetic shielding material, and the Ni sheet accounts for 25% of the total mass of the electromagnetic shielding material, and the preparation method thereof comprises the following steps:
[0069] 1. Ti 3 C 2 T x Preparation of nanosheets: First, prepare 40 ml of 9 mol / L HCl solution and add it to a polytetrafluoroethylene beaker for later use. Then add 2 g of LiF powder to the polytetrafluoroethylene beaker and stir it magnetically in a 38°C water bath for 20 minutes. 3 AlC 2 Slowly add a small amount of the solution to the container for etching reaction. After 48 hours of reaction, centrifuge at 4750 rpm and wash the precipitate with deionized water several times until the pH is 6. Then treat with a high-power ultrasonic machine (180 W, 40 min), then centrifuge (4750 rpm, 10 min), and finally collect the black upper suspension in the centrifuge tube.
[0070] 2. 5 ml of MXene suspension was filtered into a membrane using a vacuum filtration device (the diameter of the device was 55 mm, the pressure was 5000 Pa, the membrane material was cellulose membrane, and the pore size was 0.22 um). After drying and peeling off the membrane, the mass was measured and the concentration was 7 mg / ml.
[0071] 3. Add FeCo alloy particles with a diameter of 1 to 2 μm and a mass of 75 mg into 20 ml of deionized water, and add 20 mg of SDBS, and disperse by ultrasound at an ultrasonic power of 160 W and an ultrasonic time of 15 min to obtain a 3.75 mg / ml FeCo alloy particle dispersion.
[0072] 4. Add Ni flake powder with a diameter of 1 to 5 μm and a mass of 75 mg into deionized water, and add 20 mg SDBS, and ultrasonically disperse it with an ultrasonic power of 160 W and an ultrasonic time of 15 min to obtain a 3.75 mg / ml Ni flake dispersion.
[0073] 5. Take 21.5 ml of the MXene suspension obtained in step 1, 20 ml of the FeCo alloy dispersion with a concentration of 3.75 mg / ml obtained in step 3, and 20 ml of the Ni flake dispersion with a concentration of 3.75 mg / ml obtained in step 4, mix and shake well, and disperse by ultrasound at an ultrasonic power of 160 W and an ultrasonic time of 15 min to obtain Ti 3 C 2 T x MXene / FeCo / Ni mixed dispersion.
[0074] 6. The uniform dispersion obtained in step 5 is rapidly frozen with liquid nitrogen.
[0075] 7. The frozen mixture obtained in step 6 was placed in a freeze dryer and vacuum dried for 36 hours to obtain Ti 3 C 2 T x MXene / FeCo / Ni composite powder.
[0076] The structural diagram of the composite material is shown in Figure 1 As shown in the figure, the large flake structure is the MXene obtained by etching, the spherical structure embedded in it is the FeCo alloy microsphere, and the small flake structure is the Ni sheet. Figure 2 As shown, it can be seen that the three materials of flaky MXene, FeCo alloy magnetic microspheres, and flaky Ni are well mixed, and the magnetic alloy microspheres and Ni sheets are embedded in the MXene interlayer more evenly.
[0077] The composite material prepared in Example 1 was doped with 30 mg of paraffin wax and pressed into a coaxial ring with an outer diameter of 7 mm and an inner diameter of 3 mm. The S parameters of the coaxial ring were measured in the range of 2-18 GHz using a vector network analyzer in a coaxial air line. The results are as follows: Figure 3 As shown. Figure 3 The average electromagnetic shielding effectiveness of the composite material in Example 1 is 46.2 dB. The average electromagnetic shielding effectiveness in the S band is 37.3 dB, the average electromagnetic shielding effectiveness in the C band is 40.9 dB, the average electromagnetic shielding effectiveness in the X band is 46.2 dB, and the average electromagnetic shielding effectiveness in the Ku band is 52.6 dB, with the highest electromagnetic shielding effectiveness reaching 57.2 dB.
[0078] Example 2
[0079] The MXene-based electromagnetic shielding material anchored with a 0 / 2-dimensional magnetic metal provided in this embodiment, wherein the FeCo alloy particles account for 16.7% of the total mass of the electromagnetic shielding material, and the Ni sheet accounts for 16.7% of the total mass of the electromagnetic shielding material, and the preparation method thereof comprises the following steps:
[0080] According to Example 1, the experimental conditions of step 1 to step 2 are completely the same.
[0081] 3. Add FeCo alloy particles with a diameter of 1 to 2 μm and a mass of 50 mg into 20 ml of deionized water, and add 20 mg of SDBS, and disperse by ultrasound at an ultrasonic power of 160 W and an ultrasonic time of 15 min to obtain a 2.5 mg / ml FeCo alloy particle dispersion.
[0082] 4. Add Ni flake powder with a diameter of 1 to 5 μm and a mass of 50 mg into deionized water, and add 20 mg SDBS, and disperse by ultrasound at an ultrasonic power of 160 W and an ultrasonic time of 15 min to obtain a 2.5 mg / ml Ni flake dispersion.
[0083] 5. Take 28.5 ml of the MXene suspension obtained in step 1, 20 ml of the FeCo alloy dispersion with a concentration of 2.5 mg / ml obtained in step 3, and 20 ml of the Ni flake dispersion with a concentration of 2.5 mg / ml obtained in step 4, mix and shake well, and ultrasonically disperse at an ultrasonic power of 160 W and an ultrasonic time of 15 min to obtain Ti 3 C 2 T x MXene / FeCo / Ni mixed dispersion.
[0084] According to Example 1, the experimental conditions of steps 6 and 7 are exactly the same.
[0085] The composite material prepared in Example 2 was doped with 30 mg of paraffin wax and pressed into a coaxial ring with an outer diameter of 7 mm and an inner diameter of 3 mm. The S parameters of the coaxial ring were measured at 2 to 18 GHz using a vector network analyzer in a coaxial air line. The results are as follows: Figure 4 As shown. Figure 4 The average electromagnetic shielding effectiveness of the composite material in Example 2 is 51.2 dB. The average electromagnetic shielding effectiveness in the S band is 39.4 dB, the average electromagnetic shielding effectiveness in the C band is 43.1 dB, the average electromagnetic shielding effectiveness in the X band is 50.0 dB, the average electromagnetic shielding effectiveness in the Ku band is 61.2 dB, and the highest electromagnetic shielding effectiveness can reach 69.8 dB.
[0086] Comparative Example
[0087] The comparative example provides a pure MXene electromagnetic shielding material, and the preparation method thereof comprises the following steps:
[0088] According to Example 1, the experimental conditions of step 1 and step 2 are exactly the same.
[0089] 3. Take 42.8 ml of the MXene suspension obtained in step 1 and quickly freeze the suspension with liquid nitrogen.
[0090] 4. Place the frozen mixture in a freeze dryer and vacuum dry for 36 hours to obtain Ti 3 C 2 T x MXene powder.
[0091] The composite material prepared in the comparative example was doped with 30 mg of paraffin wax and pressed into a coaxial ring with an outer diameter of 7 mm and an inner diameter of 3 mm. The S parameters of the coaxial ring were measured at 2 to 18 GHz using a vector network analyzer in a coaxial air line. The results are as follows: Figure 5 As shown. Figure 5 , the average electromagnetic shielding effectiveness of the composite material in the comparative example is 40.2dB. The average electromagnetic shielding effectiveness in the S band is 38.5dB, the average electromagnetic shielding effectiveness in the C band is 38.4dB, the average electromagnetic shielding effectiveness in the X band is 40.0dB, the average electromagnetic shielding effectiveness in the Ku band is 45.1dB, and the highest electromagnetic shielding effectiveness can reach 42.0dB. Compared with the pure MXene electromagnetic shielding material in the comparative example, the material in the above embodiment of the present invention has a higher electromagnetic shielding capability within a wider frequency band, indicating that by introducing magnetic alloy microspheres and flaky magnetic metals into MXene materials to form a composite material, the electromagnetic shielding effectiveness of the composite material can be significantly improved.
[0092] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various modifications or variations within the scope of the claims, which does not affect the essence of the present invention. The above preferred features can be used in any combination without conflicting with each other.
Claims
1. A MXene-based electromagnetic shielding material anchored with a 0 / 2-dimensional magnetic metal, characterized in that: The electromagnetic shielding material includes MXene material, nearly 0-dimensional magnetic alloy microspheres and 2-dimensional flaky magnetic metals. The MXene material has a lamellar structure. The magnetic alloy microspheres and the flaky magnetic metals are embedded between the lamellar layers of the MXene material. The mass of the magnetic alloy microspheres accounts for 8.3%-33.3% of the total mass of the electromagnetic shielding material, and the flaky magnetic metal accounts for 8.3%-33.3% of the total mass of the electromagnetic shielding material.
2. The MXene-based electromagnetic shielding material anchored with a 0 / 2-dimensional magnetic metal according to claim 1, characterized in that: The MXene material is a MAX phase ceramic.
3. The MXene-based electromagnetic shielding material anchored with a 0 / 2-dimensional magnetic metal according to claim 1, characterized in that: The particle size of the MXene material is 200-400 mesh.
4. The MXene-based electromagnetic shielding material anchored with a 0 / 2-dimensional magnetic metal according to claim 1, characterized in that: The magnetic alloy microspheres are any one of magnetic FeCo microspheres, magnetic CoNi microspheres and magnetic FeNi microspheres; and the diameter of the magnetic alloy microspheres is 1-10 μm.
5. The MXene-based electromagnetic shielding material anchored with a 0 / 2-dimensional magnetic metal according to claim 1, characterized in that: The flaky magnetic metal is any one of nano-flaky nickel, nano-flaky iron and nano-flaky ferroferric oxide; the side length of the flaky magnetic metal is 1-20 μm.
6. A method for preparing a MXene-based electromagnetic shielding material anchored with a 0 / 2-dimensional magnetic metal according to any one of claims 1 to 5, characterized in that: include: Providing a MXene suspension; Adding magnetic alloy microspheres into deionized water, then adding anionic surfactant, and ultrasonically dispersing to obtain a magnetic alloy microsphere dispersion; Adding flaky magnetic metal powder into deionized water, adding anionic surfactant, and ultrasonically dispersing to obtain flaky magnetic metal dispersion; The MXene suspension, the magnetic alloy microsphere dispersion and the flaky magnetic metal dispersion are mixed and uniformly dispersed by ultrasonication to obtain a composite liquid; Rapidly freezing the composite liquid with liquid nitrogen to form a shape; The freeze-formed mixture is vacuum dried to obtain anchored 0 / 2-dimensional magnetic metal MXene-based electromagnetic shielding material powder.
7. The method for preparing a MXene-based electromagnetic shielding material anchored with a 0 / 2-dimensional magnetic metal according to claim 6, characterized in that: The method of providing a MXene suspension comprises: adding MAX phase ceramic powder into an etching solution, stirring in a water bath, then centrifugally washing with water, and then ultrasonically dispersing to obtain a MXene suspension.
8. The method for preparing a MXene-based electromagnetic shielding material anchored with a 0 / 2-dimensional magnetic metal according to claim 7, characterized in that: The etching solution is a HCl / LiF composite solution.
9. The method for preparing a MXene-based electromagnetic shielding material anchored with a 0 / 2-dimensional magnetic metal according to claim 6, characterized in that: The anionic surfactant is any one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and sodium dioctyl sulfosuccinate.
10. Use of the electromagnetic shielding material according to any one of claims 1 to 5 or the electromagnetic shielding material prepared by the method according to any one of claims 6 to 9, characterized in that: The MXene-based electromagnetic shielding material is applied to any one of MEMS sensor packaging, automotive electronic products, stealth fighters and wearable electronic devices.
Citation Information
Patent Citations
MXene-based flexible polyvinyl alcohol electromagnetic shielding composite film and preparation method thereof
CN112876712A
High-absorption type electromagnetic shielding composite film
CN113583273A
MXene-based composite material as well as preparation method and application thereof
CN113950236A
Two-dimensional FeNi3-coated MXene nano-structure electromagnetic wave low-frequency absorbing material and preparation method thereof
CN116847644A
MXene / ferrite composite electromagnetic shielding fabric and preparation method thereof
CN117926582A
Cited By
Electromagnetic wave shielding element, formulation, preparation method and electromagnetic wave shielding device
WO2026152494A1